An Overview on Staining Potential of Root Canal Irrigants and Medicaments in - Mathur, Nitish; S Nath, Kartik; Nasir Khan, Yusuf Md; Singh, Anupam; Nagpal, Tarun; Kothari, Prashant (International Journal of Psychosocial Rehabilitation, 2020)
Success of endodontic treatment depends upon eliminating microorganisms from the root canal. Thus, disinfection in endodontics is a critical step which relies on root canal irrigants and intracanal medicaments. This review aims to discuss the intrinsic and internalized staining potential of routinely used root canal irrigants and intracanal medicaments in endodontic practice. Keeping in mind the antimicrobial effect of irrigants and intracanal medicaments, the dentist should also consider their staining potential and measures to prevent the same. Thus, endodontic treatment should not focus only on biological and functional aspects, but also consider aesthetic consequences as well.